Comparative approach of triage’s legal regulation - Douvika, Eleni (Elena) (Bioethica, 2022)
Triage is defined as the sorting of patients in the absence of available health resources. It is a practice that has been used in different forms from ancient Egypt to the present day. Due to the COVID-19 pandemic, this practice intensified and consequently both ethical and legal issues began to arise. The health professional, should the screening be done without any state directive or should the state mechanism regulate the exact framework of screening? Who is responsible for screening options? What screening criteria are ethical? These are the main questions arising from this practice. This paper attempts to answer these questions by analysing and comparing the different legal frameworks of different states, and ultimately proposing an optimal legal framework for the practice of triage.